Effectiveness and safety of non-tumor necrosis factor inhibitor therapy for anti-human T-cell leukemia virus type 1 antibody-positive rheumatoid arthritis. Issue 5 (3rd September 2021) - Endo, Yushiro; Fukui, Shoichi; Umekita, Kunihiko; Suzuki, Takahisa; Miyamoto, Junya; Morimoto, Shimpei; Shimizu, Toshimasa; Koga, Tomohiro; Kawashiri, Shin-ya; Iwamoto, Naoki; Ichinose, Kunihiro; Tamai, Mami; et al.
Abstract: Objectives: Our previous study showed that the effectiveness of tumor necrosis factor (TNF) inhibitors was attenuated in anti-human T-cell leukemia virus type 1 (HTLV-1) antibody-positive patients with rheumatoid arthritis (RA). We aimed to evaluate the effectiveness and safety of non-TNF inhibitors in anti-HTLV-1 antibody-positive patients with RA. Methods: We reviewed patients with RA who received abatacept or tocilizumab as the first biologic agent. We used the data of patients treated with TNF inhibitors from our previous study to compare the effectiveness between the anti-HTLV-1 antibody-positive patients treated with TNF inhibitors and non-TNF inhibitors using the inverse probability of treatment weights (IPTW) method. Results: A total of 359 patients were divided into anti-HTLV-1 antibody-negative and -positive patients of 332 and 27, respectively. No statistically significant difference was observed in the change in the clinical disease activity index between the anti-HTLV-1 antibody-positive and -negative patients. The results using the IPTW method showed a significant association between the non-TNF inhibitors treatment and a better response. None of the patients developed adult T-cell leukemia/lymphoma or HTLV-1-associated myelopathy/tropical spastic paraparesis during the 24 weeks. Conclusion: Our results indicate that non-TNF inhibitors treatment is safety, and the effectiveness is not attenuated also in anti-HTLV-1 antibody-positive patients.